The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1101/231209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

System drift and speciation

Abstract: Even if a species' phenotype does not change over evolutionary time, the underlying mechanism may change, as distinct molecular pathways can realize identical phenotypes. Here we use quantitative genetics and linear system theory to study how a gene network underlying a conserved phenotype evolves, as the genetic drift of small changes to these molecular pathways cause a population to explore the set of mechanisms with identical phenotypes. To do this, we model an organism's internal state as a linear system o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 131 publications
3
42
0
Order By: Relevance
“…Previous authors have noted that Fisher's model predicts this pattern (Barton 2001; Fraïsse et al. 2016b; Schiffman and Ralph 2017), and here, we extend this insight to give formal conditions for Haldane's Rule. We will assume identical selection in both sexes, and that pure‐species individuals of both sexes have the same fitness.…”
Section: Results With Haploid Geneticsmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous authors have noted that Fisher's model predicts this pattern (Barton 2001; Fraïsse et al. 2016b; Schiffman and Ralph 2017), and here, we extend this insight to give formal conditions for Haldane's Rule. We will assume identical selection in both sexes, and that pure‐species individuals of both sexes have the same fitness.…”
Section: Results With Haploid Geneticsmentioning
confidence: 60%
“…For example, previous authors have shown that Fisher's model predicts Haldane's Rule: the tendency of sex‐specific breakdown to appear in the heterogametic sex (Haldane 1922; Turelli and Orr 2000; Barton 2001; Fraïsse et al. 2016b; Schiffman and Ralph 2017; see Fig. 1 C).…”
Section: Models and Resultsmentioning
confidence: 93%
“…First, stabilizing selection might maintain the phenotype at a (more-or-less) stationary optimum, while still allowing for divergence at the genomic level, perhaps by nearly neutral evolution. This is sometimes called "system drift" (Barton 1989;Mani and Clarke 1990;Hartl and Taubes 1998;Rosas et al 2010;Schiffman and Ralph 2017), and it is illustrated in Figure 3c. Alternatively, divergence could involve adaptation to a moving optimum, but with a complex pattern of environmental change, e.g., with an optimum that oscillated back and forth; this is illustrated in Figure 3d.…”
Section: Hybrid Fitness and The Process Of Divergencementioning
confidence: 99%
“…So far, we have ignored an implausible prediction of Fisher's model. Equation 20, predicts that fully heterozygous hybrids will always be as fit as their parents, because, when p 12 = 1 and h = 1/2, the benefits of heterozygosity exactly cancel the costs of hybridity (Barton 2001;Fraïsse et al 2016;Schiffman and Ralph 2017).…”
Section: Phenotypic Dominancementioning
confidence: 99%
See 1 more Smart Citation